Effect of Different Catalysts on Properties of Coal Tar Pitch Modified by Cinnamaldehyde - Wenjuan Zhang; Wenhong Tian; Shihua Song; Xianren Zeng; Peng Gao; Lili Mao; Tiehu Li (Journal of Spectroscopy)
Cinnamaldehyde- (CMA-) modified coal tar pitches (CTPs) are prepared in the presence of acids. In this paper, the effect of boric acid and p-toluene sulfonic acid on the pyrolysis and graphitization process of CMA-modified CTP was studied. The pyrolysis process was studied by Fourier transform infrared spectroscopy, thermogravimetric analysis and derivative thermogravimetry, and polarized-light microscopy. In addition, the graphitization process was studied by X-ray diffraction and Raman spectroscopy. The results indicate the carbon yield of CMA-modified CTP with boric acid as catalyst (B7C10) is higher than that of CMA-modified CTP with p-toluene sulfonic acid as a catalyst (P7C10). In addition, under the same experimental condition (heated at 400°C and held for 1 h), the mesophase spheres of B7C10 are more regular than those of P7C10 and the largest diameter of the mesophase spheres can reach to 40 um. Further, after the graphitization process, the graphitization degree of B7C10 is higher than that of P7C10. So, it is more effective to modify CTP with boric acid as a catalyst.